Genetic divergence in the Indian Mackerel Ra,~trelliger kanagurta (Cuv) from the coastal waters of Peninsular India and the Andaman Sea - Menezes, Maria R; Naik, Sandeep; Martins, Maria (Indian Journal of Fisheries, 2011)
One important consideration in the commercialexploitation of a fishery resource isthe identificat;on of any discrete population orstock units. These stock units are usually selfmaintaininggroups offish that are temporallyor spatially isolated from one another. Becauseof their isolation it is assumed that theyare genetically distinct (Booke 1981).